A New Date for Concrete in Rome*. (November 2015) - Mogetta, Marcello
Abstract: Concrete is regarded as a quintessentially Roman achievement. The spread of the technology is usually dated to the fourth or third centuriesb.c ., and interpreted as a symptom of Rome's early expansion in Italy. In this paper I offer a reappraisal of the available evidence for early concrete construction in Rome. On the basis of stratigraphic evidence, I conclude that a later date should be assigned to most of the remains. I situate the origins of the technological innovation within the radical change in architectural styles that unfolded in the middle of the second centuryb.c ., affecting both domestic architecture and public building. The new chronology has an impact on current models of cultural diffusion in Roman Italy, linking the development of Late Republican architecture with the broader debate on the cultural implications of the Roman conquest.